İNGİLİS DİLİNDƏ NİSBİ ƏVƏZLİKLƏR VƏ ONLARIN AZƏRBAYCAN DİLİNDƏ QARŞILIĞI - Hüseynova Aynur (European Research Materials, 2024)
The article elaborates the relative pronouns in English and Azerbaijani languages. The differences and similarities between Azerbaijani and English Relative Pronouns were brought into noticle in the study. Besides, specific features of Conjunctive, Interrogative and Exlamatory Pronouns have been discussed in detail. It has been noted that Conjunctive and Relative pronouns resemble to each other. Conjunctive pronouns are met in Subject, Object, Predicate and Adverbial clauses while Relative pronouns are found in Attribute clauses. For the first time, Exclamatory Pronouns have been devised and used by Babayev Javid.